The evolution of music - Townsend, P. D. (Oxford University Press, 2020)
This volume explores some of the very strong links between music and advances in science. It contains many original perceptive insights, from why music evolves, to the political influences of music, and even how new streaming techniques could undermine the music industry.
10.1093/oso/9780198848400.001.0001
Keywords: Music and technology